Ecological crisis and cultural representation in Latin America : ecocritical perspectives on art, film, and literature - Anderson, Mark, 1974-; Bora, Zélia (Ecocritical theory and practice., 2016)
This book approaches portrayals of environmental crises in Latin American nations in literature, film, performance, and digital art within the context of the ongoing expansion of globalized neoliberal capitalism from and ecocritical perspective, focusing not only on the representation of ecological crises and their effects, but also their transformative potential and possibilities for generating sustainable futures.